EFFECT OF Clitoria ternatea INFUSION ON THE NEUTROPHIL CELLS AND LYMPHOCYTE CELLS IN A MODEL OF Salmonella typhimurium INFECTION - Anggia Destiawan, Rian; Imroatul Muflihah, Ahdiah; Hidayati, Sholihatil; Hariani Nurjanah, Mutia; Sandi Basuki, Aditya Occy; Asista Indarusanti, Delvia; Hayati, Farhatul; Amalia, Nabila (Jurnal Biosains Pascasarjana, 2024)
Salmonellosis is caused by infection with the bacterium Salmonella sp. which causes immune dysregulation and damage to digestive epithelial cells. So there is a need to increase immunity to fight Salmonella sp. The purpose of this study is to determine the effect of telang flower infusion on the number of Nuetrophophil cells and Lomfosyte cells on Salmonella typhimurium infection. The study was divided into 6 groups, negative, positive, Stimuno (0.26ml/20gBB), therapy 1 (0.25 ml/20gBB), therapy 2 (0.5 ml/20gBB), therapy 3 (1 ml/20gBB). Infusion making, Bacterial infection, infusa therapy, Giemsa staining, and 95% p-value data analysis. The results showed that there was a significant difference in the number of neutrophil cells in each group (p<0.05). Meanwhile, the number of lymphocytes after the anova test showed a significant increase in the number of lymphocytes (0.00<0.05). The conclusion of this study is that the infusion of telang flowers from low to high doses has an effect on increasing the number of neutrophil cells and lymphocyte cells